Bone marrow‐on‐a‐chip: Long‐term culture of human haematopoietic stem cells in a three‐dimensional microfluidic environment. (5th November 2017) - Sieber, Stefan; Wirth, Lorenz; Cavak, Nino; Koenigsmark, Marielle; Marx, Uwe; Lauster, Roland; Rosowski, Mark
Abstract: Multipotent haematopoietic stem and progenitor cells (HSPCs) are the source for all blood cell types. The bone marrow stem cell niche in which the HSPCs are maintained is known to be vital for their maintenance. Unfortunately, to date, no in vitro model exists that accurately mimics the aspects of the bone marrow niche and simultaneously allows the long‐term culture of HSPCs. In this study, a novel three‐dimensional coculture model is presented, based on a hydroxyapatite coated zirconium oxide scaffold, comprising of human mesenchymal stromal cells (MSCs) and cord blood derived HSPCs, enabling successful HSPC culture for a time span of 28 days within the microfluidic multiorgan chip. The HSPCs were found to stay in their primitive state (CD34 + CD38 − ) and capable of granulocyte, erythrocyte, macrophage, megakaryocyte colony formation. Furthermore, a microenvironment was formed bearing molecular and structural similarity to the in vivo bone marrow niche containing extracellular matrix and signalling molecules known to play an important role in HSPC homeostasis. Here, a novel human in vitro bone marrow model is presented for the first time, capable of long‐term culture of primitive HSPCs in a microfluidic environment.